Solar irrigation pumps: can electricity buy-back curb groundwater over-use? - Franklin, Bradley (2015)
Groundwater pumping for irrigation has exploded across India since the 1970’s largely due to a proliferation of cheap pump sets and highly subsidized energy. In much of Western and peninsular India, aquifers have been overexploited with substantial decreases in water tables leading to even higher amounts of energy used for pumping. As solar irrigation pumps become more effective and affordable, the prospect of uncontrolled solar pumping further exacerbating the unsustainable use of groundwater has led to calls by some for the government to buy back excess electricity generated on farms. Under such a scheme, the buy-back price would have to be high enough to make selling the power more profitable than using it for further irrigation, yet not as high as the price that is charged for electricity from the grid lest an opportunity for arbitrage be created. The correct value for the buy-back price will thus depend on the marginal profitability of water use on the farm with the possibility that the value of water to the farmer may be too high to make the scheme feasible. In this paper, estimates of water and electricity demand are derived for Punjab state and used to inform what an effective buyback scheme might entail. Results indicate that a buy-back price differentiated by season and location might be an affordable way to promote groundwater conservation.